Analisis Konten Video Animasi Youtube Sebagai Media Pembelajaran Biologi Pada Materi Sistem Peredaran Darah Di SMA: Penelitian - Alfira, Annisa; Ardi, Ardi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to reveal the level of suitability of the content of the circulatory system material animation video on the YouTube platform with the Learning Outcomes (CP) and Learning Objectives (TP) of the Independent Curriculum Phase F. The large selection of animated videos available on the YouTube platform is important to evaluate the feasibility and suitability of the videos with the learning objectives of the independent curriculum and biology learning matrix for high school students in grade XI Phase F. is a type of quantitative descriptive research design content analysis (content analysis). The population in this study is all animated videos about the circulatory system on the YouTube platform with animation video samples uploaded on the Biological Asik, Gia Academy, Mr. Klik, and Bisa Pedia channels. The results of the study showed that in the aspect of the curriculum, GIA Academy (88.1%) and Asik Biology (95%) had a high suitability for learning outcomes and objectives. In the material aspect, Asik Biology (92.6%) and GIA Academy (93%) stood out in the clarity of concept and consistency of scientific terms. In the audio-visual aspect, both channels display animations that are in sync with the narrative, while Mr. Klik and Bisa Pedia are still inconsistent. From the technical aspect, GIA Academy and Biology Asik are superior to Mr.Klik and Bisa Pedia, but they are still worth using. Overall, the videos from GIA Academy and Asik Biology are considered the most suitable for the Merdeka Curriculum